História e interdisciplinaridade no processo de humanização da fisioterapia - Petri, Fernanda Calil (2006)
From reflections on some concepts related to practical the current one in the area of the health, a new form was found to work the education and the practical clinic of the physiotherapy, which are lived deeply, mainly, for the humanização of the services given to the patients. E which characteristics that possibly influence in the process of humanização of the health? Innumerable factors contribute so that it occurs, however, were chosen to work in this dissertação two of them, the interdisciplinaridade and the historical knowledge of the profession, which have importance in the development of this process, as much in the graduation how much, during the professional life. To if considering a bibliographical research concerning the influence of the interdisciplinaridade and history in the process of humanização of the physiotherapy, one gives credit that the results will be able to collaborate for generation of some changes of this proper reality. In view of the necessities of better understanding the process of humanização of the physiotherapy, inside of its historical context, it is proposal of this dissertação to reach the following objectives: From the study on history of the physiotherapy and interdisciplinaridade to verify if these factors they have influence in the process of humanização of the profession. To observe as the concepts of Inter, multi and transdisciplinaridade they can influence in the humanização of the profession. Finally, to describe and to analyze the process of humanização of the Health, and for consequence, of the physiotherapy through its relation with the Public Health and the characteristics of the Only System of Saúde (SUS). Objective thus, to contribute for the generalista formation and humanist of the professional physiotherapist, so that, of this form, it it works next to the society, being promoted mainly, the profit of quality of life of the person human being. This dissertação is composed in 4 chapters: The first chapter, History of the physiotherapy , rescues the history of the profession since the century passed until the present, passing for its insertion in the Mercosul. In the context of Brazil, the text starts leaning over itself on the historical rescue of the physiotherapist since the coming of the Real Family to the country. As the chapter, Interdisciplinaridade , approach the different forms of Inter-relations between the professions and you discipline them, as well as works the differences between the terms to transdisciplinar, to multidiscipline and to interdisciplinar. The interdisciplinaridade inside of the area of the health is boarded and also its relation in the physiotherapy. In the third Chapter, Humanização , is worked the vision of health and illness first, and, then after, the possible factors are verified that promote the humanização of the health and the physiotherapy. In the four chapter, it has a personal story of experience as teacher in Period of training Supervised in physiotherapy in the Collective Health, in the University of Santa Cruz of the South. Through this story, a successful example of humanização in the atendimentos is demonstrated, through the influence of the interdisciplinaridade and the politics-social conscience of the graduation pupils. In the final considerações the old and current models of health are rethink that permeiam the physiotherapy as profession of the health, as well as some conclusions on humanização and interdisciplinaridade are weighed.